Rethinking social protection policy for persons with disabilities in Ghana - Naami, A.; Mor, K.S.T.; Pumpuni, C.M.; et al. (African Journal of Social Work, 2024)
Globally, social protection plays a pivotal role in poverty reduction and has been adopted to address the needs of vulnerable populations in society, including persons with disabilities. Social protection is an essential mechanism to achieve sustainable development. The United Nations’ Agenda 2030 Sustainable Development Goals seek, among others, to ensure that state parties implement social protection which could prevent situations that adversely impact the well-being of their poor citizens. Poverty lingers in Ghana, despite interventions developed under the National Social Protection Policy. Disability is a social, economic, mental, and public health issue with over a billion of the world’s population living with some form of disability. Persons with disabilities are disproportionately poor because of challenges and barriers to their inclusion and full-effective participation in society. Guided by the Convention on the Rights of Persons with Disabilities and the Sustainable Development Goals, we conducted a content analysis of the National Social Protection Policy of Ghana. Twin-track approach to social policy development, modification to existing social protection programmes and the inclusion of persons with disabilities in decision-making processes are among the recommendations to address the needs of persons with disabilities in Ghana.
Research Article
Keywords: disability; Ghana; social protection